2017
DOI: 10.1111/1462-2920.13952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of coastal phytoplankton composition estimated from the V4 and V9 regions of the 18S rRNA gene with a focus on photosynthetic groups and especially Chlorophyta

Abstract: We compared the composition of eukaryotic communities using two genetic markers (18S rRNA V4 and V9 regions) at 27 sites sampled during Ocean Sampling Day 2014, with a focus on photosynthetic groups and, more specifically green algae (Chlorophyta). Globally, the V4 and V9 regions of the 18S rRNA gene provided similar images of alpha diversity and ecological patterns. However, V9 provided 20% more OTUs built at 97% identity than V4. 34% of the genera were found with both markers and, of the remnant, 22% were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 56 publications
4
84
1
Order By: Relevance
“…These discrepancies limit comparability of bacterial and fungal diversity using rRNA gene sequences. For example, in a simpler application involving only eukaryotes, Tragin et al (2018) found that V4 and V9 regions of 18S rRNA genes in phytoplankton samples had similar levels of a-diversity, but the V9 region identified 20% more OTUs. To address these issues, we constrained fungal and bacterial comparisons in four ways.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies limit comparability of bacterial and fungal diversity using rRNA gene sequences. For example, in a simpler application involving only eukaryotes, Tragin et al (2018) found that V4 and V9 regions of 18S rRNA genes in phytoplankton samples had similar levels of a-diversity, but the V9 region identified 20% more OTUs. To address these issues, we constrained fungal and bacterial comparisons in four ways.…”
Section: Discussionmentioning
confidence: 99%
“…The European Ocean Sampling Day project (OSD) sampled the world coastal waters in 2014 around the summer solstice (21 June) with the aim of analyzing the diversity and distribution of marine microorganisms 7 especially in coastal waters using 18S rRNA metabarcodes (V4 and V9 hyper-variable regions) 8 . This dataset allowed to determine the distribution of fourteen classes of Chlorophyta 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The short and hyper-variable V4 and V9 fragments only provide partial phylogenetic signal of the full SSU-rRNA locus , which is in-turn, only an approximation of the real protistan phylogenetic relatedness as assessed with whole genome sequencing (Burki, 2014). Besides, the genetic distances estimated between these two hyper-variable regions can be the same or drastically different depending on which taxa are being compared (Dunthorn, Klier, Bunge, & Stoeck, 2012;Hu et al, 2015;Tragin, Zingone, & Vaulot, 2018). The congruent results for protistan co-occurrences and co-exclusions derived from both pairwise sequence distances and phylogenetic distances shows that both type of distances can be used to infer phylogenetic relatedness.…”
Section: Discussionmentioning
confidence: 94%